Makna Kisah Panggilan Para Murid Yesus Bagi Metode Pendidikan Agama Kristen: The Meaning Of Jesus Disciples’ Vocation For The Christian Education Method - Yusuf Siswantara (Reformed Center for Religion and Society, 2021)
Jesus is a teacher who sets an example of His teaching to the disciples. The story of the early disciples' vocation provides evidence that Jesus is expertise in personal development. This fact is a moral criticism issue that is not in line with religious values and a challenge to Christian religious education which means the Church work in the educational issue. Through a library research approach, this study aims to explore the pedagogical meaning and methods of Christian religious education in vocational stories (Matthew 4: 18-22, Markus. 1: 16-20, Luke 5: 1-14). The focus is on the pedagogical meaning, methodology and implementation of the teachings of Jesus in the vocational story. The result is an imaginative analogy, a term that affirms the educational meaning of Christian religious and educational methodology where the experience (in the light of) faith is accompanied by acts that are much more effective in Christian religious education. Keywords: Pedagogy; Educational Methods; Christian Religious Education; Disciples of Jesus.